Marginal and internal fit of CAD CAM system: A literature review - Ahad Al-shalan; Arwa A-lmutair; Diaa Aldin; Shahad Bin-Abbas; Mlaa Al-shmlani; Zahra Asif (Elsevier, 2019)
The marginal and internal fit are the critical factors for a successful prosthesis. So the aim of this article is to cover all the aspects regarding the measurement methods for the marginal and internal gap, Factors influencing marginal and internal adaptation in CAD/CAM system from scanning to machining and the effect of CAD/CAM Martials in the marginal and internal adaption. Materials and methods: An electronic search of MEDLINE (PubMed) and the search included English-language.The following keywords were combined 'CAD/CAM' with 'Marginal', 'Internal', 'Precision', 'Fit', 'Adaptation', 'Discrepancy', 'Accuracy', 'Gap', 'impressions.', 'intra-oral scanner,', 'extra-oral scanner', 'subtractive', 'additive'. Discussion and results: Most of these studies with different method of examination marginal and internal fit and various influencing factor that affect CAD/CAM adaption it makes difficult in definitive conclusion on the adaptability of CAD/CAM prostheses. Despite of these factors most of the studies shown that the marginal and internal fit clinically acceptable. However most of these studies were in vitro studies tested under ideal conditions, that's not reflect the clinical environment such as presence of saliva or blood and restricted mouth opening which can limit the accuracy of digital oral scanner. Further studies are necessary to assess the fit accuracy of CAD/CAM restorations under clinical conditions. Conclusion: McLean and von Fraunhofer have suggested that 120 μm should be the limit for clinical use. Most of these studies proved that CAD/CAM systems are able to manufacture prosthesis with clinically accepted marginal gap.